Accelerated senescence as a cost of reproduction: Testing associations between oxidative stress and reproductive effort in rural and urban women. Issue 6 (14th November 2020) - Sancilio, Amelia; Jasienska, Grazyna; Panter‐Brick, Catherine; Ziomkiewicz, Anna; Nenko, Ilona; Bribiescas, Richard G.
Abstract: Objectives: Oxidative stress is hypothesized to contribute to age‐related somatic deterioration. Both reproductive and ecological context may necessitate tradeoffs that influence this outcome. We examined whether measures of lifetime reproductive effort were related to levels of oxidative stress biomarkers in peri‐ and post‐menopausal women and whether associations were moderated by rural or urban residence. Methods: We surveyed 263 healthy women (age 62.1 ± 10.0 SD) from rural (N = 161) and urban Poland (N = 102), collecting sociodemographic data and urine samples to analyze biomarkers of oxidative stress (8‐oxo‐2′‐deoxyguanosine, 8‐OHdG) and antioxidative defense (copper‐zinc superoxide dismutase, Cu‐Zn SOD). Linear regression models, adjusted for residence, were used to test for associations between reproductive effort and 8‐OHdG and Cu‐Zn SOD. Results: Univariate models demonstrated significant associations between gravidity and the biomarkers of oxidative stress (8‐OHdG: R 2  = 0.042, P  ≤ .001; Cu‐Zn SOD: R 2  = 0.123, P  ≤ .001). Multivariate models incorporating potential confounding variables, as well as cross‐product interaction terms, indicated that gravidity was associated with 8‐OHdG ( P  < .01, R 2 adj  = 0.067) and Cu‐Zn SOD ( P  = .01, R 2 adj  = 0.159). Residence (ie, urban vs rural) did not significantly moderate the associations between the biomarkers and reproductive effort. Conclusions: Higher lifetime reproductive effort contributes to increases in oxidative stress and antioxidative defenses. Our results provide evidence of potential mechanisms underlying the physiological tradeoffs influencing senescence for women with high reproductive effort. We illustrate the value of applying an evolutionary perspective to elucidate variation in human health and senescence.